Supercritical Carbon DioxideâBased Sterilization of Decellularized Heart Valves - Ryan S. Hennessy, MD; Soumen Jana, PhD; Brandon J. Tefft, PhD; Meghana R. Helder, MD; Melissa D. Young, PhD; Rebecca R. Hennessy, MD; Nicholas J. Stoyles, BS; Amir Lerman, MD (JACC: Basic to Translational Science, 2017)
Summary: Sterilization of grafts is essential. Supercritical carbon dioxide, electrolyzed water, gamma radiation, ethanol-peracetic acid, and hydrogen peroxide techniques were compared for impact on sterility and mechanical integrity of porcine decellularized aortic valves. Ethanol-peracetic acidâ and supercritical carbon dioxideâtreated valves were found to be sterile using histology, microbe culture, and electron microscopy assays. The cusp tensile properties of supercritical carbon dioxideâtreated valves were higher compared with valves treated with other techniques. Superior sterility and integrity was found in the decellularized valves treated with supercritical carbon dioxide sterilization. This sterilization technique may hold promise for other decellularized soft tissues. Key Words: decellularized, decontamination, heart valve, tensile properties, tissue engineering